Anticancer Activity of 1-Phenylnaphthalene and Pericarbonyl Lignans - Deo, Sujata; Inam, Farhin; N. Jadhav, Anupama (Asian Journal of Chemistry, 2012)
1-Phenyl naphthoic acid, its methyl ester and pericarbonyl lignan lactone system were synthesized and studied for their anticancer activity using MTT assay. The results were found to be significant, causing the inhibition of MCF-7 cells by tumor necrosis factor alpha (TNF-a) and showed a dose dependent inhibition of MCF-7 cells.